Self-reported physical activity levels and clinical progression in early Parkinson's disease. (April 2019) - Amara, Amy W.; Chahine, Lana; Seedorff, Nicholas; Caspell-Garcia, Chelsea J.; Coffey, Christopher; Simuni, Tanya; ,
Abstract: Introduction: This study investigates longitudinal changes in self-reported physical activity, measured by Physical Activity Scale of the Elderly (PASE), in early Parkinson's disease (PD) and matched healthy control (HC) participants in the Parkinson's Progression Marker Initiative (PPMI) and evaluates associations between physical activity and PD progression. Methods: PPMI is a prospective, longitudinal study evaluating markers of progression in PD participants who are unmedicated at enrollment. PASE, a self-reported measure of physical activity, was administered to early PD (N = 380) and HC (N = 174). PASE was introduced after study launch and therefore administered at years 2, 3, and 4. PASE scores for PD and HC were compared with t-tests and changes over time were evaluated with generalized estimating equations. Results: There were no differences in activity levels between PD and HC at any time point. However, PD participants had a longitudinal decrease in PASE from years two to four (p = 0.034), while HC did not (p = 0.89). In exploratory analyses controlling for age, sex, and disease duration, higher self-reported activity at year 2 were associated with slower progression of motor symptoms (p = 0.018), ADL performance (p < 0.0001), depression (p = 0.001), anxiety (p = 0.002), and cognitive decline (p = 0.016) over two years. These findings remained significant after adjusting for disease severity. Conclusion: There are no differences in self-reported physical activity between HC and early PD, but activity levels decline longitudinally in PD. Exploratory analyses show that higher self-reported physical activity is associated with less disease progression. Therefore, interventions to increase physical activity in early PD could potentially modify the disease course. Highlights: Self-reported physical activity declines over time in early Parkinson's disease. Higher self-reported activity levels are associated with slower motor progression. Higher self-reported activity is associated with slower non-motor symptom decline.